Reminiscence therapy using virtual reality technology affects cognitive function and subjective well-being in older adults with dementia - Maho Tominari (Cogent Psychology, 2021)
Reminiscence therapy is garnering attention for stimulating seniors’ cognitive functions. It could be inferred that that synergistic effects could be created by combining virtual reality (VR), which can project realistic images, with recall, which stimulates memory. We hypothesized that by projecting realistic memories to stimulate recall, VR-based reminiscence therapy would stimulate cognitive function better than conventional photo-based reminiscence therapy. We randomly assigned total 52 people with mild cognitive impairment to eight weeks of reminiscence therapy using either tablet VR panoramas or conventional still photos with 26 participants in each group. Before and after therapy, we tested their cognitive functions with the mini-mental state examination (MMSE), the revised PGC morale scale, multidimensional observation scale for elderly subjects, trail making tests A and B, and the word fluency test. The total scores of MMSE showed improvement for both groups, but did not show statistical significance of the VR panoramas group over the conventional still photos group. However, of the two groups, only the VR panoramas group showed considerable improvement from the baseline. In addition, the analysis of secondary outcome showed that the revised PGC morale scale scores rose considerably higher in the VR panoramas group than in the still photos group. No definite differences were observed in other scales. Contrary to our primary hypothesis, reminiscence therapy produced cognitive improvement regardless of whether its stimuli were still photos or VR panoramas. However, the greater improvement in VR participants’ revised PGC morale scale scores shows enhancement of patients’ subjective well-being.